Determination of mineral element content of Pelargonium roseum plant by ICP-MS - Carmen Gâlea; Gabriel Hancu; Attila Csiszer; Csengele Monika Jeszenszky; Enikő Barabás (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2016)
Microelement content of different vegetative parts of Pelargonium roseum was evaluated by inductively coupled plasma - mass spectrometry (ICP-MS) technique. The analytical method allowed the determination of 20 elements (Li, Be, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Se, Rb, Sr, Ag, Cd, In, Ba, Tl, Pb, Bi). Samples from different vegetative parts (roots, lignified stems, green stalks, leafs, blooms) were analyzed and compared with soil samples. The vegetative part of the plant contained significant quantities of manganese, zinc and especially iron. The results can be very useful for the determination of the recommended doses of plant products for use in medicinal plant products considering its nutritional content and pharmacological functions.